PENGARUH KUALITAS PRODUK TERHADAP NILAI PELANGGAN DAN KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN APOTEK DELA SEMARANG - Munisih, Siti; Soliha, Euis (Proceeding Fakultas Ekonomi, 2014)
Analysis of the influence of product quality research on customer value and customer satisfaction thatimpact on customer loyalty pharmacy Dela Semarang. This study aims to: (1) analyze the effect ofproduct quality on customer value, (2) analyze the effect of product quality to customer satisfaction, (3)analyze the effect of customer value on customer satisfaction, (4) analyze the effect of customer value oncustomer loyalty, and (5) analyze the effect of customer satisfaction on customer loyalty. The datacollection method used in this study questionnaires were 120 respondents who buy drugs in Delapharmacies Semarang more than 2 (two) times. Analysis of the data using statistical analysis with thehelp of IBM SPSS 19 software program. The results showed that (1) the quality of the product positiveand significant impact on customer value, which increases the quality of the products is also increasingcustomer value, (2) the quality of the product positive and significant effect on customer satisfaction,which increases the quality of the products that customer satisfaction is also increases, (3) customervalue positive and significant effect on customer satisfaction, which increases the value of customers alsoincreased customer satisfaction, (4) customer value positive and significant effect on customer loyalty,which increases the value customers will also increase customer loyalty , and (5) customer satisfactionpositive and significant effect on customer loyalty, increase customer satisfaction which then alsoincreases customer loyalty.Keywords: Product Quality, Customer Value, Customer Satisfaction, Customer Loyalty